DETERMINAN PILIHAN MAHASISWA AKUNTANSI UNTUK BERKARIER SEBAGAI KONSULTAN PAJAK - Lubis, Luthfiatul Afifah; Puspaningsih, Abriyani ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2023)
This study aims to analyze and determine the influence of motivation, tax knowledge, employment considerations, and perceptions of an accounting students on career choices as tax consultants. The method used in determining the sample is a purposive sample method. The population in this study were active students majoring in Accounting, Faculty of Business and Economics, Islamic University of Indonesia Class of 2019 and 2020 who had taken taxation courses with a sample of 89 respondents. This study uses primary data obtained through the distribution of the Google Form Link which contains questionnaires and is distributed online. The results of this study indicate that accounting student's motivation has a positive effect on career choices as tax consultants, accounting student's tax knowledge has no effect on career choices as a tax consultant, accounting student's employment considerations have a positive effect on career choices as tax consultants and accounting student's perceptions have no negative attitude towards a career choice as a tax consultant.